MENIMBANG PEMIKIRAN MASDAR FARID MAS'UDI TENTANG DOUBLE TAXS (ZAKAT DAN PAJAK) - Taufiq Hidayat (Economica: Jurnal Ekonomi Islam, 2013)
The revenue sources of Country  in the early days of Islam, such as zakat and taxes they are jizyah, kharaj, max (customs), and 'usyr (export-import customs) and also ghanimah and fai' (spoils of war and confiscated items). For Muslims in Indonesia,in addition they have to pay taxes to the state that include property tax,commercial goods tax, goods consumption tax, fiscal when traveling abroad, income tax, etc., they also have to pay zakat that include zakat fitrah and zakat property. Thus, Indonesian Muslims have to bear double taxs, they are taxation and zakat. This academic anxiety felt by one of the Indonesian Muslim intellectual, Masdar Farid Mas'udi. Departing from that academic anxiety Masdar then pour his fresh ideas and even controversial, especially on the issue of double taxs.